Efficient power analysis for an irreversible Carnot heat engine - Yilmaz, Tamer; Durmusoglu, Yalcin (JOHN WILEY & SONS LTD, 2008)
In this paper, the finite-time thermodynamic optimization is carried out based on the efficient power criterion for an irreversible Carnot heat engine. The obtained results are compared with those obtained by using the maximum power (MP) and maximum power density (MPD) criteria. The optimal design parameters have been derived analytically, and the effect of the irreversibilities on the general and optimal performances is investigated. Maximizing the efficient power gives a compromise between power and efficiency. The results showed that the design parameter at the maximum efficient power (MEP) condition leads to more efficient engines than at the MP conditions and that the MEP criterion may have a significant power advantage with respect to the MPD criterion. Copyright (C) 2007 John Wiley & Sons, Ltd.
Keywords: performance optimization; heat engine; power density; efficient power; JOULE-BRAYTON ENGINE; DENSITY; THERMODYNAMICS; OPTIMIZATION; CRITERION; OUTPUT; Energy & Fuels; Nuclear Science & Technology